Does Corporate Governance Enhance Bank Performance? A Meta-Analysis of Global Islamic Banking - Utami, Rachma Bhakti; Damayanti, Cacik Rut (El-Barka, 2024)
As the fastest-growing segment in the global financial industry, it is interesting to see the development of Islamic Banking. Corporate governance is an essential topic in the world of business development. This research uses a meta-analysis approach to test whether corporate governance influences bank performance in Islamic banking. This research is using a meta-analysis study; this research begins by looking for what corporate governance indicators are most closely related to improving the performance of Islamic banking. This research was conducted from 2010 to 2022 and collected a database of 199 studies covering 1606 businesses of 25 distinguished published papers from the Scopus index. This research was assisted by Publish or Perish, NVivo, and JASP software. This study found that the most frequently used factors as a measurement of Sharia governance mechanism are Board Independence, Board of Director Size, Frequency of Meetings, Audit Committee, and CEO Duality, while the indicators most often used as a measurement of Islamic banking performance are Islamic banking performance as measured by Return on Assets, Return on Equity and Tobin's Q. The results of meta-analysis data processing show that board independence has a significant and positive effect on the return on assets of Islamic banking. The Islamic Bank in Indonesia suggests optimizing the position of the Board of Independence in improving Islamic banking performance.